Lenguaje escrito empleado en los mensajes de atención al cliente de la corporación nacional de telecomunicaciones - Núñez Maroto, Selena Vanessa (2019)
At present, the Information and Communication Technologies application has developed commercial activities in companies, facilitating communication with their clients as well as being a determining factor in the communication process between the writer and reader. The goal research is to analyze the written language applied in communication with the clients of the National Telecommunications Corporation (CNT). The methodology applied is qualitative to collect data and interpret it through the analysis in the context in which it is developed using a non-experimental design. An intentional sample of five hundred messages issued by CNT which was taken responding to complaints, suggestions, complaints and client information. A data collection technique, the interview and observation guide taking into account the following written language features: structure, content, writing, linguistics and spelling. The results showed that there are linguistic problems in the written messages in a 0.6% per cent such as grammatical error in the verbs conjugation and the syntax in the connectors’ application. Also, 80% evidences revealed mistakes in the punctuation signs’ practice. The implementation manual on written language in customer service or staff training on linguistics and its application in emails these errors can be reduced and thus optimize interaction with customers.